Benzyl isothiocyanate exhibits antibacterial and antibiofilm activity against Fusobacterium nucleatum while preserving viability of human bone marrow mesenchymal stem cells: an in vitro study - Almobarak, Abdulaziz A.; Alqedairi, Abdullah; Binrayes, Abdulaziz; Lambarte, Rhodanne A.; Niazy, Abdurahman A.; Aljarbou, Fahd (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRegenerative endodontic procedures require effective disinfection and preservation of stem cell viability, which are essential for successful tissue regeneration. Conventional intracanal medicaments possess antibacterial properties but may negatively impact stem cell survival. Benzyl isothiocyanate (BITC) is a bioactive compound with known antibacterial properties and favorable biocompatibility.MethodsThis study evaluated the antibacterial efficacy of BITC against Fusobacterium nucleatum in both planktonic and biofilm forms and assessed its biocompatibility on human bone marrow mesenchymal stem cells (hBMMSCs) in comparison to calcium hydroxide (Ca(OH)2). Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using microdilution and agar culture methods. Biofilm biomass was quantified using the crystal violet assay, viability was visualized through live/dead imaging, and microstructure was examined using scanning electron microscopy. Stem cell viability was evaluated using the Alamar Blue™ assay, and cell morphology was examined using inverted microscopy.ResultsBITC exhibited MIC and MBC values of 0.2% and 0.4%, respectively. At 0.2%, BITC demonstrated comparable antibacterial activity to Ca(OH)2, whereas 0.4% and 0.8% showed enhanced bactericidal effects. Notably, 0.2% and 0.4% BITC maintained hBMMSCs viability and morphology, while 0.8% BITC and Ca(OH)2 significantly reduced cell survival.ConclusionThese findings suggest that BITC could serve as a potential antimicrobial agent in regenerative endodontic treatment and future therapeutic applications.